Implementasi Program Mentoring Melalui Tutor Sebaya dalam Meningkatkan Kemampuan Membaca Al-Qur’an di MTS Al-Musyawarah Lembang - Nisa Asipa Ulhayat; Aep Saepudin; Sobar (Bandung Conference Series: Islamic Education, 2024)
Abstract. The background to this research is that many school children cannot read the Al-Qur'an well. Learning the Al-Qur'an cannot be done instantly, special learning is needed. Therefore, Mts Al-Musyawarah has a mandatory program that its students must follow, namely the Al-Qur'an Mentoring Program using the peer tutoring method. This program is designed to help students who are not yet fluent in reading the Al-Qur'an. The purpose of this research is to analyze planning, implementation, evaluation, supporting factors and obstacles in the Mentoring Program through Peer Tutors in Improving Al-Qur'an Reading Ability. The method used in this research is descriptive qualitative. The data collection techniques used were observation, interviews and documentation. The research results show that the implementation of the Mentoring program through Peer Tutors in Improving Al-Qur'an Reading Ability at Mts Al-Musyawarah Lembang is going well. Students experience an increase in reading after participating in mentoring. This program is carried out on Tuesday-Thursday using the peer tutoring method where the mentors are the upperclassmen they teach. Peer tutoring is effective in improving the ability to read the Koran because students feel comfortable, open and social support from peers increases student activity. Evaluation of the mentoring program includes attendance, student progress and mentor performance. The supporting factors for this program are the support of the school, teachers and good cooperation between mentors & coaching teachers. Meanwhile, the inhibiting factors in this program are the lack of supervisory teachers, as well as the lack of student enthusiasm. Abstrak. Latar belakang penelitian ini adalah banyaknya anak sekolah belum bisa membaca Al-Qur’an dengan baik, untuk mempelajari Al-Qur’an tidak dapat dilakukan secara instan diperlukan pembelajaran khusus. Maka dari itu Mts Al-Musyawarah memiliki program wajib yang harus diikuti oleh siswanya yaitu Program Mentoring Al-Qur’an dengan menggunakan metode tutor sebaya, program ini dirancang untuk membantu siswa yang belum lancar membaca Al-Qur’an . Tujuan penelitian ini adalah untuk menganalisis perencanaan, pelaksanaan, evaluasi, faktor pendukung dan hambatan dalam Program Mentoring melalui Tutor Sebaya dalam Meningkatkan Kemampuan Membaca Al-Qur’an. Metode yang digunakan pada penelitian ini adalah deskriptif kualitatif. Teknik pengumpulan data yang dilakukan adalah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan pelaksanaan program Mentoring melalui Tutor Sebaya dalam Meningkatkan Kemampuan Membaca Al-Qur’an di Mts Al-Musyawarah Lembang berjalan dengan baik. Siswa mengalami peningkatan membaca setelah mengikuti mentoring. Program ini dilakukan pada hari selasa-kamis dengan metode tutor sebaya dimana para mentor merupakan kakak kelas yang diajar nya. Tutor sebaya efektif dalam meningkatkan kemampuan membaca Al-Qur’an karena siswa merasa nyaman, terbuka dan dukungan sosial dari teman sebaya meningkatkan keaktifan siswa. Evaluasi program mentoring mencangkup kehadiran, kemajuan siswa dan kinerja mentor. Faktor pendukung dari program ini adalah dukungan pihak sekolah, guru dan kerjasama yang baik antara mentor & guru pembina. Sedangkan, faktor penghambat dalam program ini adalah kurangnya guru pembina, serta kurangnya semangat siswa.